2020
DOI: 10.1016/j.jenvman.2019.110061
|View full text |Cite|
|
Sign up to set email alerts
|

How urban agglomeration improve the emission efficiency?A spatial econometric analysis of the Yangtze River Delta urban agglomeration in China

Abstract: Urban areas consume more than 66% of the world's energy and generate more than 70% of global greenhouse gas (GHG) emissions. With the world's population expected to reach 10 billion by 2100, and with nearly 90% of people living in urban areas, a critical question for planetary sustainability is how the size of cities affects energy use and carbon dioxide (CO2) emissions. Are urban agglomerations more energy and emissions efficient than smaller cities? Does urban agglomeration exhibit gains from economies of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…Here, we suggest Beijing and Tianjin need to undertake more responsibilities, and policymakers should attach importance to undeveloped cities in Hebei province when setting emissions reduction goals. Due to carbon leakage having an impact on the neighboring cities, this study reminds that: when a city makes its plan to reduce carbon emissions, particularly inside the urban agglomeration, should also consider the neighboring cities as well (Yu et al, 2020). Another policy implication is that we revealed the temporal heterogeneity of emission patterns and their driving factors.…”
Section: Discussionmentioning
confidence: 69%
“…Here, we suggest Beijing and Tianjin need to undertake more responsibilities, and policymakers should attach importance to undeveloped cities in Hebei province when setting emissions reduction goals. Due to carbon leakage having an impact on the neighboring cities, this study reminds that: when a city makes its plan to reduce carbon emissions, particularly inside the urban agglomeration, should also consider the neighboring cities as well (Yu et al, 2020). Another policy implication is that we revealed the temporal heterogeneity of emission patterns and their driving factors.…”
Section: Discussionmentioning
confidence: 69%
“…It includes trade openness, capital flow, exchange of technology and ideas, labor mobility, and cultural integration. It not only promotes the accumulation of capital, technology, culture and labor, but also promotes the development of trade, affects the optimal allocation of production factors and resources, and promotes the improvement of public health service capabilities [ 33 , 34 ]. Among the 27 countries of the EU, France, Italy, Belgium and other countries have higher globalization indexes.…”
Section: Results Discussionmentioning
confidence: 99%
“…In one path, industrial integration is conducive to the formation of emerging industries in urban agglomerations; in another, significant economic externalities are generated on surrounding cities by expanding the service radius of central cities. For example, Yu et al [59] used spatial econometric analysis and found that the technological progress of a city affected not only local carbon emissions but also that of neighboring cities. Finally, with the improvement of the level of urban clusters, central cities are more closely connected with peripheral cities, forming a social production network that divides labor and leads to cooperation, accelerating the spatial concentration and diffusion of production factors such as technology, talents, and information, all of which help peripheral cities to improve productivity, save resources, and reduce emissions.…”
Section: Transmission Channels For Urban Clusters On Regional Ecologimentioning
confidence: 99%